FOOD PROCESSING WASTE IN VIETNAM: UTILIZATION AND PROSPECTS IN FOOD INDUSTRY FOR SUSTAINABILITY DEVELOPMENT - Ngo Van Tai; Vo Quang Minh; Nguyen Minh Thuy (My University, 2023)
Vietnam is a country that produces a variety of agricultural products, including vegetables, tubers, fruits, and processed products. Along with the increase in population, the demand for consumers also increases, and the by-products of farming are increasing and being discharged into the environment. This is one of the critical research issues that need to be solved to ensure sustainability in agriculture. This review summarized recent studies on familiar sources of by-products in Vietnam, such as banana peels, citrus peels, dragon fruit skins, rice bran, and rice husks, and their potential in the food industry. Some solutions are also proposed to solve and turn this low-value raw material into a high-value product and serve a variety of products and consumers in the food industry. Especially after the COVID-19 pandemic, the by-products contain valuable and reusable biological resources. These compounds could be future applications to support improving the consumer's immune system and various health benefits. Processed and utilized by-products from food production could not only help increase incomes for farmers, especially in developing countries like Vietnam but also could aid in ensuring food security and sustainability in agricultural production.
Keywords: Value added; Medicinal Plants and Neuroprotection